2021
DOI: 10.3389/fchem.2021.741058
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Testing for Multiple Cardiac Markers Based on a Snail-Shaped Microfluidic Chip

Abstract: Existing methods for detecting cardiac markers are difficult to be applied in point-of-care testing (POCT) due to complex operation, long time consumption, and low sensitivity. Here, we report a snail-shaped microfluidic chip (SMC) for the multiplex detection of cTnI, CK-MB, and Myo with high sensitivity and a short detection time. The SMC consists of a sandwich structure: a channel layer with a mixer and reaction zone, a reaction layer coated with capture antibodies, and a base layer. The opening or closing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Their detection approach shows the high-throughput capability by quantifying both IgG and IgM antibodies directly from COVID-19-positive patient plasma samples in a single instrument run. 198 Yin et al reported a sandwich structure snail-shaped microfluidic chip for the multiplex detection of cardiac markers including cTnI, CK-MB, and Myo with high sensitivity and a short detection time using the chemiluminescence method 188 (Fig. 5B).…”
Section: Multiplex Detectionmentioning
confidence: 99%
“…Their detection approach shows the high-throughput capability by quantifying both IgG and IgM antibodies directly from COVID-19-positive patient plasma samples in a single instrument run. 198 Yin et al reported a sandwich structure snail-shaped microfluidic chip for the multiplex detection of cardiac markers including cTnI, CK-MB, and Myo with high sensitivity and a short detection time using the chemiluminescence method 188 (Fig. 5B).…”
Section: Multiplex Detectionmentioning
confidence: 99%
“…They designed a microfluidic chip by utilizing a chemiluminescence (CL) detector and coating the middle of the chip, which has reaction layer based on particular antibodies. Thus, they obtained a POCT candidate which is able to diagnose three AMI-related biomarkers with higher sensitivity and within a short time of period [ 236 ].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…As an emerging manufacturing technology, 3D printing has the characteristics of individuation and high precision. It has been widely used in miniaturized mechanical and electromechanical elements to efficiently manufacture microdevices in recent years [28,29]. We used a high-precision desktop 3D printer to make the molds of the microfluidic chip (Figure 1a).…”
Section: Design and Fabrication Of The Microfluidic Chipmentioning
confidence: 99%